Exploring the Neuroprotective Role of Selenium: Implications and Perspectives for Central Nervous System Disorders - Guanning Huang; Ying Liu; Xiadong Zhu; Lizhen He; Tianfeng Chen (Exploration)
ABSTRACT Selenium (Se) is a crucial element in selenoproteins, key biomolecules for physiological function in vivo. As a selenium‐rich organ, the central nervous system can express all 25 kinds of selenoproteins, which protect neurons by reducing oxidative stress and inflammatory response. However, decreased Se levels are prevalent in a variety of neurological disorders, which is not conducive to the treatment and prognosis of patients. Thus, the biological study of Se has emerged as a focal point in investigating the pivotal role of trace elements in neuroprotection. This paper presents a comprehensive review of the pathogenic mechanism of neurological diseases, the protective mechanism of Se, and the neurological protective function of selenoproteins. Additionally, the application of Se as a neuroprotective agent in neurological disorder therapy, including ischemic stroke, Alzheimer's, Parkinson's, and other neurological diseases, is summarized. The present review aims to offer novel insights and methodologies for the prevention and treatment of neurological disorders with trace Se, providing a scientific basis for the development of innovative Se‐based neuroprotectants to promote their clinical application against neurological diseases.